2010
DOI: 10.2319/022310-113.1
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of brackets bonded with hydrophilic and hydrophobic bond systems under contamination

Abstract: Objective: To compare, in vitro, the shear bond strength (SBS) of two bond systems: Transbond XT/XT primer (TXT/XT) and Transbond Plus Color Change/Transbond Self Etching Primer (TPCC/ TSEP). Materials and Methods: Each system was examined under four enamel surface conditions (dry, water, saliva, and blood), and 160 bovine teeth were divided into eight groups of 20 according to enamel surface condition. Group 1 used TPCC/TSEP and Group 2 used TXT/XT under dry conditions; Group 3 used TPCC/TSEP and Group 4 used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…They concluded that under contaminated condition, SEP and MIP primer should be used in conjunction with hydrophilic adhesive system rather than hydrophobic system. In another study, Santos et al .,[13] found that bond strength of SEP was not affected by contaminants such as water, saliva and blood when it was used in conjunction with a hydrophilic adhesive. Similar results have been seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that under contaminated condition, SEP and MIP primer should be used in conjunction with hydrophilic adhesive system rather than hydrophobic system. In another study, Santos et al .,[13] found that bond strength of SEP was not affected by contaminants such as water, saliva and blood when it was used in conjunction with a hydrophilic adhesive. Similar results have been seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of humidity at the bonding area is one of the challenging situations in adhesive dentistry. Previous studies indicated that keeping saliva away from the bonding surface or to obtain a dry enamel surface by eliminating remnant water prior to adhesive application are crucial precautions to to take for long-term bond durability 2,3) . Several in vitro studies had investigated the bond strength between resin-enamel interfaces and concluded that by prevention of saliva on the enamel surface or similar water contamination, ideal dry enamel surfaces could be achieved [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…While considering the source of the humidity in oral environment, air that is exhaled through the mouth, had always been overlooked. The amount of water saturated in the exhaled air is reported to be about 27 mg/dm 3 and its possible effects on dental practice requires careful evaluation 9) . Although rubber dam can be used in routine in order to isolate the adhesive surface from the oral environment, its use could be restricted during luting laminate veneers and crowns with subgingival margins, operating in Class V lesions, bonding brackets in the posterior area or in many other chair-side conservative applications.…”
Section: Introductionmentioning
confidence: 99%
“…As blood [1, 4, 9, 13, 20], water [3, 6, 24], and saliva [3, 9, 24] contamination on shear bond strength of orthodontic brackets has been extensively tested, no studies are present about water and saliva contamination of disinclusion buttons. In the present investigation for both disinclusion buttons and orthodontic brackets, no significant differences were found between water- and saliva-contaminated groups.…”
Section: Discussionmentioning
confidence: 99%